German Insurance Industry: Market Overview and Trends - Raimond H. Maurer; Barbara Somova (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2005)
This article presents an overview of the contemporary German insurance market, its structure, players, and development trends. First, brief information about the history of the insurance industry in Germany is provided. Second, the contemporary market is analyzed in terms of its legal and economic structure, with statistics on the number of companies, insurance density and penetration, the role of insurers in the capital markets, premiums split, and main market players and their market sha res. Furthermore, the three biggest insurance lines - life, health, and property and casualty - are considered in more detail, such as product range, country specifics, and insurance and investment results. A section on regulation outlines its implementation in the insurance sector, offering information on the underlying legislative basis, supervisory body, technical procedures, expected developments, and sources of more detailed information.
Keywords: G34; G22; G28; 330; German insurance industry; market participants; market trends; regulation; Versicherung; Markt; Branchenentwicklung; Deutschland